The Failure of the Islamic Party in Indonesia to Winning the 2004-2019 Direct General Elections - Muhamad Nastain; Irwan Abdullah; Zuly Qodir; Hasse Jubba (UIN Sunan Gunung Djati, 2023)
This research aims to describe the evidence of the failure of Islamic political parties to encourage their best cadres to become national leaders (president and vice president) in direct presidential election contests from 2004-2019. Over the course of the past four election cycles, candidates affiliated with Islamic political parties have been notably absent, instead opting to form coalitions in support of candidates from other political factions. A political anomaly, where the majority of the population adheres to the Islamic faith, yet candidates from Islamic political parties are conspicuously absent. The research was conducted using the literature study method and analyzed using John Dewey's pragmatism theory approach which was strengthened by Hanna Pitkin's representation theory. Data findings are corroborated by factor analysis of the failure of Islamic political parties using NVIVO 12Plus. Data were obtain from credible offline and online sources. The main findings of this research show four key pieces of evidence. Firstly, an overview of the electoral support landscape for Islamic political parties in direct presidential elections over the four periods highlights their dominance only in the 2004 elections, followed by subsequent declines. Second, the map of the coalition of Islamic political parties in every direct election underscores their diminished influence and inability to construct an Islamic polar coalition. Third, mapping the votes of support for Islamic political parties in every election which results in stagnation of support for Islamic political parties with no more than 32%. Lastly, the study identifies the contributing factors to the failure of Islamic political parties. Islamic political parties need to formulate a comprehensive cadre system to produce cadres who are competent and have high electability to win the presidential election.